A Nanosized Codelivery System Based on Intracellular Stimuli-Triggered Dual-Drug Release for Multilevel Chemotherapy Amplification in Drug-Resistant Breast Cancer - Yufan Guo; Shuo Liu; Fazhen Luo; Dongyun Tang; Tianshu Yang; Xiuru Yang; Yan Xie (MDPI AG, 2022)
Lacking nano-systems for precisely codelivering the chemotherapeutics paclitaxel (PTX) and the natural P-glycoprotein (P-gp) inhibitor, quercetin (QU), into cancer cells and controlling their intracellular release extremely decreased the anticancer effects in multidrug resistant (MDR) tumors. To overcome this hurdle, we constructed hybrid polymeric nanoparticles (PNPs) which consist of redox-sensitive PTX/polyethyleneimine-tocopherol hydrogen succinate-dithioglycollic acid PNPs and pH-sensitive hyaluronic acid-QU conjugates. The obtained hybrid PNPs can be internalized into drug-resistant breast cancer cells by the hyaluronic acid/CD44-mediated endocytosis pathway and escape from the lysosome through the "proton sponge effect". Under the trigger of intracellular stimuli, the nanoplatform used the pH/glutathione dual-sensitive disassembly to release QU and PTX. The PTX diffused into microtubules to induce tumor cell apoptosis, while QU promoted PTX retention by down-regulating P-gp expression. Moreover, tocopherol hydrogen succinate and QU disturbed mitochondrial functions by generating excessive reactive oxygen species, decreasing the mitochondrial membrane potential, and releasing cytochrome c into the cytosol which consequently achieved intracellular multilevel chemotherapy amplification in MDR cancers. Importantly, the PNPs substantially suppressed tumors growth with an average volume 2.54-fold lower than that of the control group in the MCF-7/ADR tumor-bearing nude mice model. These presented PNPs would provide a valuable reference for the coadministration of natural compounds and anticarcinogens for satisfactory combination therapy in MDR cancers.